THE INFLUENCE OF TRANSFORMATIONAL LEADERSHIP ON EMPLOYEE PERFORMANCE MEDIATED BY WORK MOTIVATION AT THE COMMUNICATIONS AND INFORMATICS DEPARTMENT OF BINJAI CITY - Iedya Fadillah; Mesra B (Lafadz Jaya Publisher, 2023)
The purpose of this study was to determine and analyze the effect of transformational leadership on employee performance mediated by work motivation at the Office of the Office of Communication and Informatics, Binjai City. This research was carried out at the Binjai City Communication and Information Office. This type of research is associative quantitative. The population in this study was 90 employees with ASN and honorary status at the Binjai City Communication and Information Office. The sampling technique in this research uses a saturated sample where the entire population is sampled. The results of this study indicate that: (1) Transformational leadership has a significant effect on employee performance with a T-statistic value of 3.275 > 1.96 and a P-Value of 0.002 <0. 05, which means that if employee transformational leadership increases, employee performance will increase. (2) Transformational leadership has a significant effect on work motivation with a T-Statistic value of 20.141 > 1.96 and a P-Value of 0.000 < 0.05 or it can be interpreted that if transformational leadership is increased then work motivation will also increase. (3) Work motivation has a significant effect on employee performance with a T-Statistic value of 3.956 > 1.96 and a P-Value value of 0.000 < 0.05 or it can be stated that the higher the level of employee work motivation, the more employee performance will increase. (4) The work motivation variable can mediate the influence between transformational leadership and employee performance at the Binjai City Communication and Information Office with a T-Statistic value of 3.682 > 1.